Who Says? A review by Professional Translators of the Work of Students Translating Health Text from English into Italian - Chesher, Terry (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractA translation project is described involving translation students (non-professionals) and experienced practitioners (professionals) working on a text relating to diabetes, aimed at Italian-speakers in Australia. Professionals were interviewed as they checked the student version of the text, and a number of problems were identified which were considered to need correction or amendment. Practitioners describe their normal procedure when checking translations, and offer general impressions of the students' work. Examples are given of problem areas encountered both in the English SL text before and after pre-translation Plain English editing, and in the students' version of the Italian. A tentative Translation Accuracy schema is outlined.